Correlates of unplanned pregnancy in Ethopia: beyond individual and household factors - Olarewaju, Olajumoke Kiito (My University, 2016)
INTRODUCTION Nearly all maternal and newborn deaths take place in low and middle-income countries; and most of these deaths could be prevented. Unplanned pregnancy is a major concern from both human rights and public health perspectives. Women who experience unplanned pregnancy are not only exposed to unsafe and illegal abortion but also maternal and child morbidity and mortality. Unplanned pregnancy is a pregnancy that has been reported to be unwanted at the time of pregnancy. Studies on unplanned pregnancy in Ethiopia have focused mainly on individual-level determinants of unplanned pregnancy. The efforts to reduce the incidence of unplanned pregnancy in Ethiopia have remained weak; therefore there is the need for continued research aimed to reducing unplanned pregnancy. Hence, this study will go beyond both individuals and household levels to examine to what extent community factors moderate the association between individual or socio-demographic factors and unplanned pregnancy. The theoretical frameworks used for this study are: framework for “Analyzing the Determinants of Maternal Mortality” by James McCarthy and Deborah Maine, and “The Ecological Determinants of Health” framework by Bronfenbrenner in 1979. McCarthy and Maine framework was based on the effort to reduce maternal mortality; the concept behind the framework is the basic stages in the process that result into maternal morbidity and maternal mortality. Bronfenbrenner’s ecological theory takes into consideration that ecological model will give a holistic approach to analyze both the multilevel and the interactive influences of health outcomes. METHOD This study utilizes data from the 2011 Ethiopian Demographic and Health Survey (EDHS). The study population is women aged 15-49, who wanted pregnancy now, later or did not want pregnancy when they became pregnant (7 764). The method of analysis for this study will include descriptive analysis which includes the calculation of the rates of unplanned pregnancy, chi-square test will be carried out to identify the individual factors, household factors and community factors associated with unplanned pregnancy in Ethiopia; and then a multi-level analysis will be done to determine the extent to which contextual factors account for variations in unplanned pregnancy in Ethiopia. RESULT The preliminary results indicate that 32% of women experienced unplanned pregnancy in Ethiopia in 2011. The bivariate analysis established association between unplanned pregnancy and a number of factors such as; marital status, number of surviving children, wealth index, use of contraception, knowledge of contraception, region, community poverty, community family planning services, community female employment and community level of female education. The multilevel analysis result also identified region of residence, community poverty, community family planning services and community female employment as important contextual factors of unplanned pregnancy during the period of study. For instance, women residing in southern Ethiopia had the highest odds of unplanned pregnancy compared to other regions (odds ratio-2.8; p<0.05); those in communities with moderate concentration of family planning services had relatively higher odds compared to other groups (odds ratio-1.7; p<0.05); and those in communities with low concentration of female employment had the highest odds of experiencing unplanned pregnancy (odds ratio-2.3; p<0.05). The contextual factors in this study explained 23% of the variations in the full model. DISCUSSION AND CONCLUSION The findings of this study has demonstrated that community contexts are very important characteristics that impact on regional variations in unplanned pregnancy in Ethiopia, the results from this study suggests that there is a need to take the effects of community contexts into consideration if significant improvement is to be achieved on unplanned pregnancy.
A RESEARCH REPORT SUBMITTED TO, THE FACULTY OF HUMANITIES, UNIVERSITY OF THE WITWATERSRAND, JOHANNESBURG IN FULFILMENT OF THE REQUIREMENT FOR THE AWARD OF THE DEGREE OF MASTERS IN DEMOGRAPHY AND POPULATION STUDIES